HOUT-18. TREATMENT STRATEGIES FOR GLIOBLASTOMA IN OLDER PATIENTS: AGE IS JUST A NUMBER. (11th November 2019) - Youssef, Michael; Ludmir, Ethan; Mandel, Jacob; Patel, Akash; Jalali, Ali; Treiber, Jeffrey; Wu, Jimin; McAleer, Mary; DeGroot, John
Abstract: BACKGROUND: Optimal care for elderly patients with glioblastoma (GBM) remains in question due to their exclusion from and underrepresentation in clinical trials (including EORTC 22981) as well as their historically-poor overall survival. METHODS: Retrospective chart review was conducted at a single high-volume cancer center for newly-diagnosed elderly (65 years old or older) GBM patients diagnosed from 2011 through 2017. RESULTS: A total of 158 newly-diagnosed GBM patients aged 65 years and older were identified. 144 patients (91.1%) underwent radiation therapy. One-hundred thirty patient (90.3%) received concurrent temozolomide with radiotherapy. A minority of patients (23%) discontinued temozolomide during concurrent or adjuvant treatment due to side effects or complications of chemotherapy. Sixty-one patients (38.6%) completed concurrent chemoradiation and 6 cycles of adjuvant temodar. The median overall survival (OS) time for our cohort was 18.6 months, with estimated OS rates of 74.8%, 35.9%, and 9.5% at 1, 2, and 5 years, respectively. On multivariable analysis, higher KPS (p=0.002, HR 0.46; 95% CI: 0.63–0.82), completing planned course of radiation (p=0.01, HR 0.29; 95% CI: 0.11–0.75), and completing 6 cycles of adjuvant temozolomide (p=0.01, HR 2.62; 95% CI: 1.67–4.12) were associated with improved OS. CONCLUSIONS: Our cohort of elderly GBM patients were predominately treated with a standard of care based on EORTC 22981. Despite their age, these patients tolerated treatment well and had a favorable overall survival compared to outcomes reported for patients treated on EORTC 22981. Using age alone as the reason to de-escalate treatment or as an exclusionary criteria in clinical trials should be discouraged.